PSYCHOLOGICAL ASPECTS OF THE CONCEPT OF RELIGIOUS TOLERANCE - Obidov Asliddin Shavkatovich (Web of Journals Publishing, 2024)
This article unveils the psychological foundations of the concept of religious tolerance. It also highlights the historical roots and theoretical bases of religious tolerance. In particular, the thoughts of William James, Sigmund Freud, and Carl Jung are presented in relation to religious tolerance. The article concludes with a discussion on the implications of developing religious tolerance in various societies and proposes future research directions for a more inclusive and empathetic approach to interfaith harmony.
Keywords: tolerance, intolerance,